Improving Photovoltaic Systems in Jordan Using TRIZ Principle - Overview and Case Study - Sakhrieh, Ahmad; Al Asfar, Jamil; Ghandour, Ahmad; Adel, Ala’a (International Journal of Energy Economics and Policy, 2022)
Buildings, both residential and commercial, continue to be a major source of energy consumption in the world due to the escalating rate of global energy demand. Energy supplied to buildings through conventional means negatively impacts the environment. Due to its geographic location and climatic conditions, Jordan has a high solar energy potential. This encouraged using photovoltaic panels on building envelopes to produce electricity. One of the major problems facing this technology is the performance of the installed systems. In this context, this paper adapted the Theory of Inventive Problem Solving (also known as TRIZ) to improve the performance of photovoltaic systems; with less cost, less time, less installation place, and high output power. TRIZ principle was applied to a case study of an existing photovoltaic system in Jordan in order to study the impact of materials used in PV cells construction on a PV system’s performance. The analysis of the results show the potential of increasing the energy produced by changing the material of the PV cells. Economic analysis was also carried out for the suggested PV systems.